Scientific Communication: The Art of Preparing and Presenting Scientific Results - Ludovic Saint-Félix; Alexandre Vaz Machado; Monique Scalco; Valdenize Tiziani; Rivadávio Amorim (Brazilian Society of Geriatrics and Gerontology, 2024)
This article is part of a special series designed to help authors in the process of scientific writing and communication. The objective of the study was to provide tools and strategies to prepare and achieve effective forms of oral communication, especially related to posters and oral presentations. A non-systematic literature research (PubMed/Web of Science) was performed to retrieve relevant data about how to prepare posters, oral presentation and how to control anxiety caused by oral speeches. In addition, a brief overview of innovative and recent digital tools is also provided. The scientific literature proves some interesting recommendations for preparing a good poster or a slide show and to avoid public speech anxiety as well. A list of available digital tools for such preparation was also disclosed. The rules for oral or poster communication differ from those related to manuscript writing. The quality of oral scientific communication can be improved by following such rules.